2017
DOI: 10.1200/jco.2017.73.0143
|View full text |Cite|
|
Sign up to set email alerts
|

AKT Inhibition in Solid Tumors With AKT1 Mutations

Abstract: Purpose AKT1 E17K mutations are oncogenic and occur in many cancers at a low prevalence. We performed a multihistology basket study of AZD5363, an ATP-competitive pan-AKT kinase inhibitor, to determine the preliminary activity of AKT inhibition in AKT-mutant cancers. Patients and Methods Fifty-eight patients with advanced solid tumors were treated. The primary end point was safety; secondary end points were progression-free survival (PFS) and response according to Response Evaluation Criteria in Solid Tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
222
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(240 citation statements)
references
References 27 publications
17
222
1
Order By: Relevance
“…In most breast cancer series this is the most frequently altered potentially actionable pathway, thus these alterations are actively being pursued in trials with PI3K/AKT/ mTOR inhibitors. 2,23,24 CDH1 mutations, as expected, were almost exclusively found in invasive lobular carcinoma. CDH1 loss is pathognomonic for lobular carcinomas; the fact that we found CDH1 mutations in only 56% of patients suggests that CDH1 loss may also be mediated through non-genomic mechanisms.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In most breast cancer series this is the most frequently altered potentially actionable pathway, thus these alterations are actively being pursued in trials with PI3K/AKT/ mTOR inhibitors. 2,23,24 CDH1 mutations, as expected, were almost exclusively found in invasive lobular carcinoma. CDH1 loss is pathognomonic for lobular carcinomas; the fact that we found CDH1 mutations in only 56% of patients suggests that CDH1 loss may also be mediated through non-genomic mechanisms.…”
Section: Discussionsupporting
confidence: 84%
“…Data is emerging that targeting some of these alterations, such as AKT and HER2 mutations, indeed may have antitumor efficacy. 1,2 Most proof-of-principle genomically-selected trials are conducted in the metastatic setting, while many molecular characterization efforts such as The Cancer Genome Atlas (TCGA) were performed in operable breast cancer. 3 In order to effectively design and interpret genotype-selected trials, it is critical to determine the genomic profile of patients with metastatic breast cancer (MBC), the frequency of genomic alterations as well as co-alterations, and to determine the impact of common alterations on prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…These patients were diagnosed with one of 21 unique cancer types, the most common being breast, lung, bladder and colorectal cancer (61% of patients treated). As has been seen in other basket studies 10,11 , we identified and enrolled a number of orphan tumour types including cancers of the biliary tract, salivary gland, small bowel and vagina, as well as extramammary Paget’s disease (13% of all patients). Patients tended to be heavily pretreated with approximately half having received ≥3 prior lines of systemic therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The initial generation of these studies focused on evaluating individual somatic mutations that were already clinically validated in one cancer (eg BRAF V600 in melanoma) in other tumour types 10,35 . More recently, basket studies have been used to generate initial or even practice-changing clinical data of truly novel genomic biomarkers, especially when these genomic alterations occur at low frequency across a wide distribution of cancer types 11,36,37 . SUMMIT extends this concept one step further by demonstrating for the first time how a single study can be used to simultaneously evaluate a range of individual variants in HER2 and HER3, each with varying degrees of prior biologic characterization.…”
Section: Discussionmentioning
confidence: 99%
“…are reported. Encouraging early response rates of the use of AZD5363 (6/21, 28%) with the schedules recommended in this study have been reported (25). Further efforts to improve outcomes by combining AZD5363 with fulvestrant in AKT-mutant breast cancer is ongoing.…”
Section: Discussionmentioning
confidence: 99%